Pengaruh Jenis Sensor terhadap Persentase Eror Sensor Parkir Berbasis STM32 - Qais Rakhmanda Yoga Pratama; Asrori Asrori (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
This study evaluates the impact of sensor type on the percentage error in an STM32-based parking sensor system by comparing the HY-SRF05 and JSN-SR04T ultrasonic sensors. The aim of this research is to determine the accuracy of each sensor in distance measurement and identify the more reliable sensor for parking sensor applications. The methodology includes installing both sensors on the STM32 system, measuring distances at various intervals, and analyzing the percentage error. The results indicate that the HY-SRF05 sensor exhibits a lower percentage error compared to the JSN-SR04T across all tested distances, from 50 cm to 300 cm. The average percentage error for the HY-SRF05 is 1.78%, while for the JSN-SR04T it is 2.6%. The conclusion of this research is that the HY-SRF05 sensor is more accurate and reliable than the JSN-SR04T for STM32-based parking sensor applications.